PRESS COVERAGE OF CRISES: (A Research Drawn from a Doctoral Thesis) - Hussein al-Rubei’i, Dhamia’a . (ALBAHITH ALALAMI, 2020)
Media is one of the main and effective factors; and it is a tool of crisis management equipment. Media is one of the most dangerous, effective and decisive weapons in modern conflicts; a tool for making events and influencing their events and trends as a means of reporting as the enormous capabilities of media which help media to move very quickly, and cross borders; and overcome obstacles, through many means of audio, reading and visual. As its ability, moreover, to influence the psychological and intellectual control of communities, and behaviors.Intelligent media is, then, used in crises management and coverage. Crises have been existed with the presence of man on Earth. Their occurrence coincided with the various activities man has practiced on the planet. On an individual level, some crises pose a serious threat to human life and property.At the state level, crises can have obvious effects. In addition to increasing their burdens and responsibilities, they can lead to a radical change in the economic, political and social conditions that threaten its existence or expose it to consequences beyond its means. Therefore, the issue of crises of all kinds has become one of the most important topics of interest to researchers, especially the diversity of crises and increasing risks.All countries, without exception, are vulnerable to any kind of crises. Crises have become an integral part of the fabric of contemporary life. This leads to pay attention to the scale of crises management.Although crises media is one of the research fields that has attracted the interest of researchers and media specialists in universities and research centers European and American for more than four decades. As a result, its theoretical concepts and practical applications have been crystallized.However, Arab studies in the field of media relations with political crises and security events did not appear significantly until after the eighties of the last century.Even after the emergence of this type of specialized media studies, what exists is only the beginnings of further research and study on one hand, and the link between its theoretical and applied fields on the other.What is existed in reality is a natural extension of what is prevalent in the theories and models of media influence that preceded this kind of specialized studies.